Testing for seasonal unit roots in heterogeneous panels in the presence of cross section dependence (2007)
This paper presents two alternative methods for modifying the HEGY-IPS test in the presence of cross-sectional dependency. In general, the bootstrap method (BHEGY-IPS) has greater power than the method suggested by Pesaran [Pesaran, M.H. (2007). A simple panel unit root test in the presence of cross section dependence. Journal of Applied Econometrics, forthcoming.] (CHEGY-IPS), although for large T and high degree of cross-sectional dependency the CHEGY-IPS test dominates the BHEGY-IPS test. © 2007 Elsevier B.V. All rights reserved.